Graphene Oxide-Chitosan Network on a Dialysis Cellulose Membrane for Efficient Removal of Organic Dyes - Vo, Thi Sinh; Hossain, Muhammad Mohsin; Lim, TaeGyeong; Suk, Ji Won; Choi, Sun; Kim, Kyunghoon (American Chemical Society, 2022)
Currently, water pollution is a significant health problem for both humans and animals due to large amounts of dye-containing wastewater. Thus, polymer composite membranes (PCMs) are considered as efficient adsorption/filtration membranes that can be utilized for removing organic dyes from contaminated water/wastewater. In this study, the goal is to explore the modification of the interfacial dialysis cellulose (DC) surface through molecular interactions of an active graphene oxide-chitosan (GO-CTS) composite hydrogel (GCCH) network without the use of an external cross-linker toward an effective dye removal ability using a simple casting process and a low-cost adsorption technique, resulting in the formation of a PCM, i.e., GO/CTS/DC membrane (GCD-mems). Concomitantly, the incorporation of the GCCH network (as an active hybrid network) and DC (as a supporting material) is considered as a promising approach toward a dye-removing PCM. As a result, the GCD-mems showed that cellulose robustly interacted via the chemical bonds of the GCCH network by maintaining the three-dimensional (3D) porous layer structures, and the functional surface of the membrane was enhanced toward specific groups for an effective dye removal approach. In addition, there is a significant improvement in dye removal performance after modification of the interfacial DC surface through molecular interactions of GCCH, i.e., high adsorption capacities of cationic and anionic dye molecules on the GCD-mems, compared to the relevant GO-based adsorbents. Also, the dye flux and rejection of the GCD-mems can simultaneously remove both methylene blue and Congo red. In the adsorption, it is appropriate with the pseudo-second-order and Langmuir models corresponding to chemical adsorption and monolayer approaches, as well as physical sieving through the 3D layers of porous channels of GCD-mems during the filtration process. Moreover, the structural stability and sustainability of the PCMs are enhanced during the recycling process, and the use of ethanol in the recycling process further simplifies the process and reduces the cost of the PCMs. Thus, the GCD-mems are encouraged as potential candidates that can be applied directly in the removal of dyes from the wastewater of textile industries or selective dialysis applications.